Принципи синтезу координувальних систем автоматичного управління - Gurskiy, Alexander; Denisenko, Andrey; Dubna, Sergey (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2026)
The problem linked to the model development of the coordinating automatic control system has been solved in this scientific work. Such a task is relevant, as it is linked to increase the operational efficiency of the technological object due to the quality improvement of ratio control. As an object the steam boiler has been considered, in which it is necessary to maintain the appropriate air-fuel ratio. The article describes the stages of the model development for the coordinating automatic control system ensuring the maintenance of a given ratio between controlled variables in transient modes. The support of the set ratio is ensured by the implementation of temporal subordination for control processes. Based on the analysis of modeling results, we have made the conclusion about the expediency of using the coordinating system of automatic control. Thus, the method of stepwise synthesis for coordinating control systems was further developed.